2006
DOI: 10.1103/physrevlett.96.154502
|View full text |Cite
|
Sign up to set email alerts
|

Self-Propelled Leidenfrost Droplets

Abstract: We report that liquids perform self-propelled motion when they are placed in contact with hot surfaces with asymmetric (ratchetlike) topology. The pumping effect is observed when the liquid is in the Leidenfrost regime (the film-boiling regime), for many liquids and over a wide temperature range. We propose that liquid motion is driven by a viscous force exerted by vapor flow between the solid and the liquid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
416
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 494 publications
(440 citation statements)
references
References 19 publications
19
416
0
5
Order By: Relevance
“…As a ubiquitous phenomenon in nature, droplet motion on solid substrates has attracted great attention for decades because of the fundamental physics involved [1][2][3][4][5][6][7][8][9][10] and its relevance to a wide range of applications in chemistry, biology, and industry [11][12][13][14][15]. Though there has been extensive work on the subject, many aspects of this seemingly simple phenomenon remain issues of interest to fundamental research.…”
Section: Introductionmentioning
confidence: 99%
“…As a ubiquitous phenomenon in nature, droplet motion on solid substrates has attracted great attention for decades because of the fundamental physics involved [1][2][3][4][5][6][7][8][9][10] and its relevance to a wide range of applications in chemistry, biology, and industry [11][12][13][14][15]. Though there has been extensive work on the subject, many aspects of this seemingly simple phenomenon remain issues of interest to fundamental research.…”
Section: Introductionmentioning
confidence: 99%
“…Droplet manipulation can be obtained using passive techniques such as wettability gradients or "designed" surface textures, 1−4 as well as using active techniques where droplets may respond to external stimuli such as vibrations, 5−7 light, 8,9 electric fields, 10 acoustics, 11 magnetic fields, 12,13 or cyclical mechanical deformation of the substrate. 14 In addition to the abovementioned methods, droplet manipulation in many heat transfer applications can also be obtained passively using in situ phase change processes as exemplified by the Leidenfrost effect 15,16 (Figure 1a), self-propelled motion during evaporation, 17,18 and water droplet motion during condensation on phase change materials (PCMs). 19,20 The latter phenomenon, first reported by Steyer et al, 19 was observed during condensation of water on solid cyclohexane kept at a temperature T c below its melting temperature (T m = 6.52°C…”
Section: Introductionmentioning
confidence: 99%
“…A general description of unbiased transport of particles in nature, which is named ratchet effect, is a challenging issue with implications in distinct areas, such as in molecular motors in biology [1], nanosystems like graphene [2], control of cancer metastasis [3], micro and nanofluids [4], particles in silicon membrane pores [5], cold atoms [6], solids and drops transport using the Leidenfrost effect [7,8], quantum systems [9][10][11][12], among many others. Certainly the most relevant and common goal in describing these ratchet systems is to unveil how to control and attain an efficient transport by choosing the appropriate physical parameter combination, like temperature, dissipation, external forces etc.…”
Section: Introductionmentioning
confidence: 99%